2005
DOI: 10.1073/pnas.0506592102
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of theBacillus subtilisanti-alpha, global transcriptional regulator, Spx, in complex with the α C-terminal domain of RNA polymerase

Abstract: Spx, a global transcription regulator in Bacillus subtilis, interacts with the C-terminal domain of the ␣ subunit (␣CTD) of RNA polymerase to control gene expression under conditions of disulfide stress, which is sensed by disulfide bond formation between Spx residues C10 and C13. Here, we describe the crystal structure of the B. subtilis ␣CTD bound to oxidized Spx. Analysis of the complex reveals interactions between three regions of ''antialpha'' Spx and helix ␣1 and the ''261'' determinant of ␣CTD. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
130
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(135 citation statements)
references
References 41 publications
5
130
0
Order By: Relevance
“…Spx controls gene expression by interacting directly with the ␣ subunit of the RNA polymerase (45). The Spx-controlled trfA gene was recently shown to be required for the ability of subinhibitory concentrations of ␤-lactam antibiotics to induce the hVISA phenotype, raising the intriguing possibility that the elevated Spx level may contribute to the decreased susceptibility to daptomycin, vancomycin, and ␤-lactams (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Spx controls gene expression by interacting directly with the ␣ subunit of the RNA polymerase (45). The Spx-controlled trfA gene was recently shown to be required for the ability of subinhibitory concentrations of ␤-lactam antibiotics to induce the hVISA phenotype, raising the intriguing possibility that the elevated Spx level may contribute to the decreased susceptibility to daptomycin, vancomycin, and ␤-lactams (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…One codon change conferring the clpX suppressor phenotype was Y263C, in the ␣1 helix of the ␣CTD. The other clpX suppressor locus is the spx gene (16), the product of which interacts with the RNAP to affect transcription initiation (25,27). Subsequent structural analysis confirmed that Spx interacts with the ␣CTD of RNAP and that the binding surface includes residue Y263 of the ␣ subunit (27).…”
mentioning
confidence: 99%
“…This leads to induction of the Spx regulon, which includes trxA (encoding thioredoxin), trxB (thioredoxin reductase), and other genes that function in the oxidative stress response and in cysteine biosynthesis (10, 34). Spx-dependent activation of trxA and trxB requires interaction of the protein with RNA polymerase (RNAP) holoenzyme (33,37). This interaction also results in repression of operons that require an activator for transcription initiation (35, 54).…”
mentioning
confidence: 99%